FACTORS OF VARIABILITY OF INDICATORS OF COMPLEX PHYSICAL FITNESS OF STUDENTS - Alenurov, E.A.; Karpov, V.Yu.; Kumantsova, E.S.; Dorontsev, A.V. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to determine the values of the contributions of various factors in the variability of indicators of the complex physical fitness of university students. Methods and structure of the study. The article used methods for determining body types, the formation of healthy lifestyle skills, the harmony of physical development, somatic health and complex physical fitness: 100 m run, standing long jump, 3 × 10 m shuttle run, torso forward tilt, 3000 run m (women - 2000 m). The study was conducted in September-October 2019 at the Russian State Social University, in which 349 students took part. Results and conclusions. The research materials made it possible to determine the values ​​of the contributions of various factors to the variability of the indicators of the complex physical fitness of university students. The greatest influence was exerted by such factors as body type, medical group, physical health. This gives grounds for differentiating the estimated indicators of the complex physical fitness of university students, taking into account these factors. The results of the study indicate that the traditional generalized method of assessing the indicators of complex physical fitness of university students is not objective and requires consideration of the factors under consideration.